Dense Y-doped ion conducting perovskite films of BaZrO3, BaSnO3, and BaCeO3 for SOFC applications produced by powder aerosol deposition at room temperature. (20th March 2020) - Exner, Jörg; Nazarenus, Tobias; Kita, Jaroslaw; Moos, Ralf
Abstract: State-of-the-art solid oxide fuel cells (SOFC) are based on oxide ion conducting zirconia electrolytes, typically doped by yttria or scandia. Major drawback of these systems are their high operation temperatures of 800 °C and above. These are necessary for a sufficient ionic conductivity. Instead of oxide ions, also protonic charge carriers could be used in SOFC. The material classes of barium zirconates (BaZrO3 ), barium stannates (BaSnO3 ), and barium cerates (BaCeO3 ) are described as good proton conductors, especially when the B-site of the ABO3 perovskite structure is aliovalently doped by yttria. Their protonic conductivity values in the moderate temperature regime up to 600 °C are comparable to YSZ at 800 °C, making these compounds ideal candidates for a usage in future SOFC. Unfortunately, very high sintering temperatures up to 1800 °C are required to process dense and therefore gas-tight solid electrolyte membranes. However, a novel spray coating method called powder aerosol deposition (PAD, also known as AD) enables to form fully dense ceramic films directly at room temperature without any necessary sintering processes. Films are deposited from ceramic powders that are accelerated by a dry carrier gas flow under vacuum conditions. In this work, we investigated the film formation of three different barium based perovskite ceramics, namely yttria doped barium zirconate, barium stannate, and barium cerate by powder aerosol deposition. The optical and mechanical quality of films was evaluated using scanning electron microscopy and microhardness indentation and their crystallographic properties were characterized by X-ray diffraction. The electrical behavior was analyzed by electrochemical impedance spectroscopy and DC polarization methods up to temperatures of 1000 °C and 800 °C, respectively. Furthermore, a preliminary study about the film formation on porous electrodes was conducted. Highlights: Dense proton conducting thick-films were produced by Powder Aerosol Deposition. Densification achieved by room temperature spray-coating - no sintering required. Comprehensive study on three doped materials classes: BaZrO3, BaSnO3, and BaCeO3 . Annealed films show bulk-like electrical conductivities and ionic transfer numbers. Film deposition on porous NiO-cermet electrode as required for SOFC membranes.